Polish Emigrants on Organizational Culture of Austrian Companies = Polscy emigranci o kulturze organizacyjnej austriackich firm - Chmielewska-Muciek, Dorota (Zielona Góra: Faculty of Economics and Management Press)
The paper is of theoretical and empirical character. It outlines considerations and studies pertaining to the perception of organizational culture of Austrian companies by Polish emigrants. When undertaking employment abroad, emigrants face a challenge of adapting to a new environment. The adaptation pertains to several aspects.
Keywords: emigranci polscy; kultura organizacyjna przedsiębiorstwa; przedsiębiorstwa austriackie; polish emigrants; organizational culture of companies; Austrian enterprises